2022
DOI: 10.3390/min12121518
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Characteristics of Soils to the Impact of Diamond Mining in Siberia (Russia)

Abstract: This article presents the results of long-term research and monitoring of the soil cover exposed to the impact of the mining and processing plant developing diamond deposits in the northeast of Siberia. The soil collection includes 436 samples of different types of Cryosols. Soil pH; soil organic carbon (SOC); granulometric composition; and mobile forms of Pb, Ni, Mn, Cd, Co, Cr, Zn, Cu, and As were identified in the samples. Multivariate statistics of the correlation matrix, clustering analysis (CA), and prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Therefore, high concentrations of these elements are explained by the second entry into the surface layer of soil in the form of re-suspended dust of soil material as a result of aerogenic spread from drilling and blasting, wind erosion of dumps, etc., as well as the influence of anthropogenic and industrial activities on the territory of the industrial site of the Udachny MPD. The studies conducted by Rodriguez Martín et al [65] and Gololobova [66] also revealed a high correlation between these elements. The Cd-Zn association suggests that these elements may come from similar sources.…”
Section: Descriptive Statistics Of Physicochemical Properties and Pte...mentioning
confidence: 79%
“…Therefore, high concentrations of these elements are explained by the second entry into the surface layer of soil in the form of re-suspended dust of soil material as a result of aerogenic spread from drilling and blasting, wind erosion of dumps, etc., as well as the influence of anthropogenic and industrial activities on the territory of the industrial site of the Udachny MPD. The studies conducted by Rodriguez Martín et al [65] and Gololobova [66] also revealed a high correlation between these elements. The Cd-Zn association suggests that these elements may come from similar sources.…”
Section: Descriptive Statistics Of Physicochemical Properties and Pte...mentioning
confidence: 79%
“…It is possible that an underground landfill and a tailings dump could indirectly affect the state of the vegetation of the territory and contribute to the formation of oxalate, since highly mineralized waters possess a calcium chloride composition; their release could trigger excessive accumulation of calcium in lichens. Results of the study of the formation conditions of calcium oxalates on the territory of the Daldyn kimberlite field revealed that calcium oxalates synthesize lichens, therefore demonstrating a protective reaction due to changes in the micro-and macronutrient composition of natural soils [61]. Lichens change the shape of the growth of thalli and accumulation of a high number of oxalates, which also according to [11] occurs during granulation of the thallus; in this case, the podecia covered with granules show a higher capacity for the accumulation of heavy metals.…”
Section: Discussionmentioning
confidence: 99%
“…With rapid industrialization, various anthropogenic activities (e.g., treated and recycled minerals, product manufacturing, burning fuels (particularly coal) and developing new oil fields, modern agricultural practices, and waste disposals contribute to the release of heavy metals [ 2 ]. Once metals (such as Hg, Cd and Pb) enter into the atmosphere, they can be transported over long distances by air currents, leading to the dramatic increase of heavy metal content in remote areas [ 3 , 4 , 5 , 6 ]. In addition, through drainage, atmospheric bulk deposition, and soil erosion, heavy metals are prone to enter into water bodies and disturb the aquatic ecosystem [ 7 ].…”
Section: Introductionmentioning
confidence: 99%